Caregiving actions: Outgrowths of the family caregiver's conceptions of care. (1st July 2013) - Aga, Fekadu; Nikkonen, Merja; Kylmä, Jari
Abstract Caregiving actions emanate from the family caregiver's care meanings. Therefore, this article presents caregiving actions as outgrowths of the family caregiver's cultural conceptions of care and as situated within constraining sociocultural factors. Qualitative data were collected through interviews and participant observations from 18 purposively selected family caregivers of people living with HIV/AIDS (PLWAs) in Addis Ababa, Ethiopia. Three lines of caregiving actions performed by the participating family caregivers are presented: nutritional and medication care actions, physical care actions, and psychological and spiritual care actions. We have also explicated the problematic situations and sociocultural factors constraining the family caregivers in performing the caregiving actions. This study underlines the significance of addressing such problematic situations as are raised, as well as the sociocultural issues that constrain the family caregivers' agentic scope for planning and executing caregiving actions.